2022
DOI: 10.1002/cam4.4755
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a combined apoptosis and hypoxia gene signature for predicting prognosis and immune infiltration in breast cancer

Abstract: Background: Breast cancer (BC) is the most common malignant tumor worldwide. Apoptosis and hypoxia are involved in the progression of BC, but reliable biomarkers for these have not been developed. We hope to explore a gene signature that combined apoptosis and hypoxia-related genes (AHGs) to predict BC prognosis and immune infiltration. Methods:We collected the mRNA expression profiles and clinical data information of BC patients from The Cancer Genome Atlas database. The gene signature based on AHGs was const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 80 publications
1
6
0
Order By: Relevance
“…31 Recent findings corroborate the prognostic prowess of a 16-gene signature involving MAP2K6 in breast cancer patients, further emphasizing its significance. 32 Additionally, SDC1 emerges as an independent prognostic risk factor associated with poor overall survival in breast cancer, 33 reinforcing the implications of the current findings. Collectively, these observations underscore the substantial value of the MAP2K6 gene in the model that was constructed in the current study.…”
Section: Discussionsupporting
confidence: 71%
“…31 Recent findings corroborate the prognostic prowess of a 16-gene signature involving MAP2K6 in breast cancer patients, further emphasizing its significance. 32 Additionally, SDC1 emerges as an independent prognostic risk factor associated with poor overall survival in breast cancer, 33 reinforcing the implications of the current findings. Collectively, these observations underscore the substantial value of the MAP2K6 gene in the model that was constructed in the current study.…”
Section: Discussionsupporting
confidence: 71%
“…The Nup107-160 complex potentially facilitates the nuclear translocation of phosphorylated ERK to control the malignant transformation of senescent cells [45,46]. NUP43 overexpression contributes to the advancement of multiple malignant cancers, including gastric cancer, breast cancer, and ovarian cancer [47][48][49]. Nevertheless, the role of NUP43 in CRC has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, RCL1 has shown strong potential for predicting overall and disease-free survival of HCC patients [ 46 ], while FANCI has been identified as a reliable marker of hepatitis B virus-associated HCC [ 47 ]. Previous studies have indicated that RCL1 could independently predict breast cancer prognosis [ 48 ] and copy number variants of RCL1 are associated with a range of neuropsychiatric phenotypes [ 49 ]. Above all, our study showed that SORBS2, FANCI, DHRS1, and IGFALS can be mutated in HCC, and the effects of these mutations should be explored in future work.…”
Section: Discussionmentioning
confidence: 99%